Thyroid Involvement in Hepatitis C Virus-Infected Patients with/without Mixed Cryoglobulinemia - Clodoveo Ferri; Michele Colaci; Poupak Fallahi; Silvia Martina Ferrari; Alessandro Antonelli; Dilia Giuggioli (Frontiers in Endocrinology, 2017)
Thyroid involvement is a common condition that can be recorded during the natural course of different systemic rheumatic diseases, including the mixed cryoglobulinemia (MC) syndrome or cryoglobulinemic vasculitis. MC is triggered by hepatitis C virus (HCV) chronic infection in the majority of cases; it represents the prototype of autoimmune-lymphoproliferative disorders complicating a significant proportion of patients with chronic HCV infection. HCV is both hepato- and lymphotropic virus responsible for a great number of autoimmune/lymphoproliferative and/or neoplastic disorders. The complex of HCV-related hepatic and extrahepatic manifestations, including MC and thyroid involvement, may be termed “HCV syndrome.” Here, we describe the prevalence and clinico-serological characteristics of thyroid involvement, mainly autoimmune thyroiditis and papillary thyroid cancer, in patients with HCV syndrome with or without cryoglobulinemic vasculitis.